Proteção aos direitos humanos e inclusão social do grupo vulnerável representado por pessoas submetidas à medida de segurança, por imposição da lei penal brasileira - BRITO, Paulo Juaci de Almeida (Universidade Federal do Pará, 2017)
Based on the assumption that the mental disorders patients treatment, disciplined in the Brazilian legal system, prevail by the segregation resulted by the security measure obligation due to the practice of law facts typified as crimes. The social inclusion is one of the Federative Republic of Brazil essential goals and the Human Dignity, the citizenship and the political plurality are some of the basic principles informers of Democratic State of Law. For an inclusive socially treatment of mental disorders patients, it needs to give them socializing ways and citizenship rights exercises, on equal terms to all free and able citizens, because any State behavior that hinders or impedes the treatment and reduce their fundamental rights affront their dignity, is in a country legal system conflict. After the Law 10.216/2001 advent, the State can’t lay on the penalties security measure indefinitely anymore, otherwise it causes serious damage to the Human Dignity, because, if it aims the mental patients treatment, this one only admits this person hospitalization for the necessary time to stabilize their mental processes, with a view to provide his social life. Thereby, it establishes in the country the lunatic asylums judiciary extinction tends. The social life and the citizenship exercise are necessary parts of these people treatment, so the best procedure applied to the people with mental disorders who have committed facts typified as crimes in Brazil takes place in Minas Gerais and Goiás States, which develop singled comprehensive care programs, that provide a multidisciplinary team, based on the bioethical intervention model, the opportunity to play an intermediary role between the patient and: a) the Judicial Courts; b) a psychosocial care system that replaces asylums; c) clinics and hospitals that realize the hospitalization and treatment; and d) the general society and family in special. This program's efficiency made recurrence fall to 6% in Goiás State and less than 3% in Minas Gerais State. In other States it varies between 60 and 85%. This is the socially inclusive security measure. Finally, the research proposes some practical measures for social inclusion, which can be performed by the socially inclusive security measure.